The Prospects for Decolonising Qur’ān and Tafsīr Studies in Indonesian Islamic Universities: A Static Discourse? - Alif Jabal Kurdi (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2026)
The discourse on decolonizing Qur’ān and tafsīr studies has gained increasing attention following Joseph E. Lumbard’s critique of the dominance of Eurocentric epistemologies in Islamic studies. While this debate has stimulated critical reflection within Western scholarship, its reception and development in Indonesian Qur’ānic studies remain underexamined. This article investigates how the discourse has evolved in Indonesian Islamic universities by focusing on the reception of Western scholarship, the predominance of contextual interpretation, and the position of tafsīr Nusantara within contemporary Qur’ānic studies. This study employs qualitative library research using critical discourse analysis. Drawing on scholarship on decolonization, Western Qur’ānic studies, Indonesian Islamic higher education, and tafsīr Nusantara, it critically evaluates the conceptual assumptions underlying the Indonesian discourse rather than measuring institutional trends. The study finds that the decolonization of Qur’ānic and tafsīr studies in Indonesia remains largely a static discourse. Although Western scholarship has been widely incorporated into academic institutions, it has primarily reinforced the dominance of contextual hermeneutics while leaving the classical Islamic exegetical tradition and tafsīr Nusantara insufficiently integrated as autonomous epistemic resources. The article argues that meaningful decolonization requires not the rejection of Western scholarship but the reconstruction of a genuinely pluralistic epistemology that recognizes classical Islamic scholarship and tafsīr Nusantara as active intellectual traditions. In doing so, it offers a critical framework for advancing decolonization in Indonesian Qur’ānic and tafsīr studies.